Metaverse and Spiritual Challenges: A Quranic Contemplation Perspective on Moral Values in the Virtual World: (Metaverse dan Tantangan Spiritual: Perspektif Tadabur Al-Qur’an terhadap Nilai Moral dalam Dunia Virtual) - Ma'ruf Wahyu Kawiriyan; Ade Nailul Huda; Samsul Ariyadi (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2025)
This research explores the harmonization between the metaverse world and Qur'anic values through a Qur'anic contemplation approach, given that the virtual technology revolution has opened up new dimensions in human activities. Although physically confined to one room, the immersive technology of the metaverse allows its users to live a comprehensive virtual life, ranging from working, socializing, playing games, running a business, and realizing aspirations that are difficult to achieve in real-world life. The realism of this increasingly sophisticated virtual environment presents its own challenges in distinguishing the boundaries between the real and virtual worlds, underscoring the need to integrate Qur'anic values as a guide, so that humanity does not fall into a virtual illusion. Through a literature study with a comprehensive Qur'anic contemplation approach to verses about wishful thinking, this research identifies six fundamental values that can be implemented in interactions with the metaverse world including the avoidance of fanaticism without the basis of knowledge, the use of Islamic teachings as a parameter of truth, the avoidance of heinous and unlawful acts, vigilance against worldly pleasures, the search for sustenance through halal channels, and a commitment to honesty in every virtual activity. These values form a comprehensive ethical framework to ensure that the use of metaverse technology aligns with Islamic spiritual and moral principles.